Knowledge-management issues in China's hotel industry. (March 2016) - Wong, Tommy; French, Linda; Wickham, Mark
Highlights: Empirically explores knowledge management processes in China's hotel industry. Presents three knowledge management issues inherent to China's hotel industry. Links Knowledge management practices to employer/industry-of-choice. Links knowledge management to employee recruitment, motivation and retention. Presents a research agenda for knowledge management in China's hotel industry.